2021
DOI: 10.1021/acsaelm.1c00754
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap-Tunable (Mg, Zn)SnN2 Earth-Abundant Alloys with a Wurtzite Structure

Abstract: Herein, wurtzite-type MgSnN2–ZnSnN2 alloys (Mg x Zn1–x SnN2) are proposed as earth-abundant and band gap-tunable semiconductors with fundamental band gaps in the range of 1.5–2.3 eV. The alloys do not exhibit immiscibility, unlike the InN–GaN system, because the lattice mismatch between the endmembers is smaller than 1% in both a- and c-axis directions. The Mg x Zn1–x SnN2 alloys can be epitaxially grown on GaN(001) in the whole x range, and their fundamental band gap can be tuned from 1.5 to 2.3 eV with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…It has been reported that sputtered films and high-pressure synthesized powders of MTN are often contaminated with oxygen. ,, Thus, the oxygen concentrations in the precursor and high-pressure heat-treated films with x = 0.02 were semi-quantitatively measured with XPS depth profiling. Figure a,b shows the depth profiles of the oxygen concentration (represented by the O/(N + O) atomic ratio) for the wz-MTN precursor layer and the high-pressure heat-treated rs-MTN films, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that sputtered films and high-pressure synthesized powders of MTN are often contaminated with oxygen. ,, Thus, the oxygen concentrations in the precursor and high-pressure heat-treated films with x = 0.02 were semi-quantitatively measured with XPS depth profiling. Figure a,b shows the depth profiles of the oxygen concentration (represented by the O/(N + O) atomic ratio) for the wz-MTN precursor layer and the high-pressure heat-treated rs-MTN films, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The oxygen concentrations within the film were comparable with or lower than the values reported for sputtered wz-MTN films. 20,22 The oxygen contamination is believed to have originated from water vapor in the residual gas within the sputtering chamber. High-pressure heat treatment promoted oxygen contamination in the surface region (Figure 7b), thereby widening the oxygen-rich surface region.…”
Section: High-pressure Heat Treatment Of Wz-mtn Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This material system attracts considerable attention, partially due to its strong similarities to the parent material system, i.e., the AlN-InN-GaN system, where the III-nitride cation is substituted by heterovalent group-II and -IV cations. For the ternary nitride system used for band gap engineering, e.g., Zn(Sn, Ge)N 2 [1] or (Zn,Mg)SnN 2 [2], ZnSnN 2 exhibits the lowest band gap for this category of materials, as summarized in the review by Greenaway et al [3]. In particular, ZnSnN 2 is of specific interest in applications of II-IV nitrides as top cell components in tandem solar cells together with silicon, as the band gap is close to the optimum for the top cell.…”
Section: Introductionmentioning
confidence: 99%
“…MgGeN 2 and MgSnN 2 have smaller band gaps of 3.2 eV [8] and 2.3 eV [9], respectively. Their counterparts in Zn-IV-N 2 family are of 3.7 eV [10], 3.1 eV [11] and 1.5 eV [9]. However, more works are still needed for further understanding of this class of materials in order to boost their applications, e.g., Dumre et al studied three crystal forms of MgSnN 2 on their mechano-electronic properties and bonding properties [12].As known, some II-IV-N 2 compounds can be used for nonlinear optical applications.…”
mentioning
confidence: 99%